TEACHERS AND STUDENTS PERCEPTION ON THE FREQUENT TEST: VOCABULARY COURSE - Wahyuningtyas, Elizabeth Wulan; Wulandari, Fransiska Selvy (LLT Journal: A Journal on Language and Language Teaching, 2017)
Through frequent test, students have higher self-motivation to understand every material in order to make them prepared in attending frequent test. This paper aims to see the teachers and students perceptions on frequent test. In addition, as the further finding, the writers will focus on the benefits of frequent test. The paper is an observation paper that focused on students and teachers perception through frequent test, and its benefits. The finding shows that both of the teachers and students show the positive perspective toward frequent test. Thus, frequent test is beneficial to both, the teachers and the students in learning process, even though there are also the negative effects.